A Compact Full 2π Flexoelectro‐Optic Liquid Crystal Phase Modulator. Issue 12 (9th November 2020) - Wang, Xiuze; Fells, Julian A. J.; Shi, Yuping; Ali, Taimoor; Welch, Chris; Mehl, Georg H.; Wilkinson, Timothy D.; Booth, Martin J.; Morris, Stephen M.; Elston, Steve J.
Abstract: Wavefront shaping, which is often achieved using liquid crystal (LC) spatial light modulators, is particularly important for a wide range of applications including laser microfabrication and micromanipulation, microscopy, and quantum optics. In this work, results are presented for the first integrated LC phase modulator that combines a flexoelectro‐optic LC layer (that behaves as a switchable λ/2 waveplate) with a polymerized reactive mesogen layer (which acts as a λ/4 waveplate) and a mirrored substrate that creates a double‐pass geometry. For a flexoelectro‐optic LC layer that exhibits switching angles of ±45° at a voltage of ±85 V a full 2π phase modulation is observed when driven by a 1 kHz waveform. Experimental results are also compared with modeling using Jones calculus of the amplitude and phase variation when the LC and the polymer layer deviate from their desired waveplate conditions. The development and demonstration of an integrated device is particularly significant for applications where size and cost are critical factors such as in LiDAR for the Space and Automotive industries, respectively. Abstract : The paper demonstrates an integrated optical phase modulator consisting of a flexoelectro‐optic liquid crystal (LC), which acts as a half‐wave plate, a polymerized reactive mesogen layer, which acts as a quarter‐wave plate, and a silvered substrate. These layers result in a 2 p optical phase modulation when the optic axis of the LC layer is switched through an angle of 90°.